Preparation and Mechanical Properties of Continuous Carbon Nanotube Networks Modified Cf/SiC Composite - Lei Wang; Feng Hou; Xin Wang; Jiachen Liu; Anran Guo (Advances in Materials Science and Engineering)
Continuous carbon nanotube (CNT) networks were formed in Cf/SiC composites via freeze-drying method. Composites were fabricated by precursor infiltration and pyrolysis (PIP) process afterwards. The different distribution morphologies of CNTs in the preforms originating from the different CNT contents were analyzed while the influence of the distribution of CNTs was discussed in detail. Compared to composites without CNTs, the interfacial shear strength (ILSS) and the flexural strength of Cf/1%CNTs/SiC were increased by 31% and 27%, respectively, but the values of Cf/2.5%CNTs/SiC decreased as a result of lots of defects caused by excess CNTs. With the analysis of ILSS, the flexural strengths, and the fracture morphologies, CNTs effectively improved the weak interfacial strength between T700SC carbon fibers and SiC matrix.